ANALYSIS OF THE STRUCTURE, CONDUCT AND PERFORMANCE OF PADDY RICE MARKETING IN WESTERN AGRICULTURAL ZONE OF BAUCHI STATE, NIGERIA - Obiora, J.C.; Danwanka, H.A.; Murtala, N. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study analyzed the structure, conduct, and performance of paddy rice marketing in the western agricultural zone of Bauchi State, Nigeria. A multi-stage sampling technique was employed to select 122 respondents from the study area. Data were collected using structured questionnaires and analyzed using descriptive statistics, Gini coefficient, budgeting techniques, and regression analysis. Results revealed that 67.2% of marketers were male, 67.2% were married, and 43.4% had attained secondary education. Business was the primary occupation for 48.4% of respondents, while 62.3% were not members of any cooperative association. The Gini coefficient of 0.76 indicated a high level of income inequality among paddy rice marketers. The purchase price of paddy rice was ₦35,000, with a total marketing cost of ₦607.24 per bag and a resale price of ₦48,870.96, resulting in a net marketing margin of ₦13,263.72 and a return on investment of 0.4. Regression analysis revealed that age (P < 0.01), household size (P < 0.05), educational level (P < 0.05), years of marketing experience (P < 0.01), transportation cost (P < 0.05), and tax (P < 0.01) significantly influenced the marketing margin. Conversely, marital status had no significant effect (P > 0.05). Major constraints identified included high transportation cost (99.2%), seasonality of supply (94.3%), price fluctuation (89.3%), and poor road network (83.6%), among others. The study concludes that paddy rice marketing in the study area is profitable, despite the existence of income inequality and structural challenges. It is recommended that marketers form cooperatives to improve access to credit and transportation, while government interventions should focus on improving road infrastructure, stabilizing market prices, and providing timely and accurate market information systems to enhance efficiency and profitability.